'Drops in the Ocean': The Politics and Practice of Policing the West Riding of Yorkshire in the Mid-Nineteenth Century. (11th April 2022) - Taylor, David
Abstract : The article examines the development of the superintending constable system in the West Riding and argues that the system, despite its limitations, was more acceptable and successful than contemporary critics and many later historians have claimed. Further, it also played an important but overlooked part in the transition to a county-wide police force following the 1856 County and Borough Police Act. Rather than being on the wrong side of history, the superintending constable system in the West Riding was an important part of a complex and evolving pattern of policing. Misleading distinctions between 'old' and 'new' policing obscure the realities of police reform in which continuities, downplayed by reformers at Westminster, played a crucial role.